Disclosure of disease status among employed multiple sclerosis patients: Association with negative work events and accommodations. (February 2015) - Frndak, Seth E; Kordovski, Victoria M; Cookfair, Diane; Rodgers, Jonathan D; Weinstock-Guttman, Bianca; Benedict, Ralph HB
Background: Unemployment is common in multiple sclerosis (MS) and detrimental to quality of life. Studies suggest disclosure of diagnosis is an adaptive strategy for patients. However, the role of cognitive deficits and psychiatric symptoms in disclosure are not well studied. Objective: The goals of this paper were to (a) determine clinical factors most predictive of disclosure, and (b) measure the effects of disclosure on workplace problems and accommodations in employed patients. Methods: We studied two overlapping cohorts: a cross-sectional sample ( n = 143) to determine outcomes associated with disclosure, and a longitudinal sample ( n = 103) compared at four time points over one year on reported problems and accommodations. A case study of six patients, disclosing during monitoring, was also included. Results: Disclosure was associated with greater physical disability but not cognitive impairment. Logistic regression predicting disclosure status retained physical disability, accommodations and years of employment ( p < 0.0001). Disclosed patients reported more work problems and accommodations over time. The case study revealed that reasons for disclosing are multifaceted, including connection to employer, decreased mobility and problems at work. Conclusion: Although cognitive impairment is linked to unemployment, it does not appear to inform disclosure decisions. Early disclosure may help maintain employment if followed by appropriate accommodations.